Peningkatan Pengetahuan Masyarakat Poto’an Daya Kecamatan Palengngaan Kabupaten Pamekasan tentang Pakan Tambahan “Kue Sapi” untuk Ternak Ruminansia - Riszqina Riszqina; Zulfaini Shamad; Cepryana Sathalica Widyananda; Joko Purdiyanto (Darmabakti : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The UNIRA Faculty of Agriculture Lecturer's Community Service Program (PPM) collaborated with the Rumah Cahaya Village Library (PERPUSDESRC) Poto'an Daya Village, Palengngaan District, Pamekasan Regency to increase ruminant livestock production in the village, it is necessary to increase public knowledge of additional feed from agricultural waste, one of which is the addition of Urea Molasses Block (UMB) with additional herbal components to increase appetite, reduce worm contamination, and increase microbial synthesis in the rumen, known as catle cake. The participation method is used in preparing plans, implementing actions and discussing priority programs to be implemented with Partner representatives. There were 19 members who took part in the training, based on the results of the pre and post test participants' understanding of knowledge about feed, livestock needs and utilization of feed ingredients¸, the difference was not too large. Overall, there was a change in participants' understanding of doubts about the use and processing of additional feed in the form of catle cake.